Beginning XNA 3.0 Game Programming - Lobão, Alexandre Santos (Apress, 2012)
According to the point-of-sale information compiled by NPD Group (http://www.npd.com), a leading US marketing information provider, computer and video game sales totaled more than seven billion dollars in each of the past three years. The video game software industry accounts for more than six billion dollars of this total. If we include portable and console hardware, software, and accessory sales, in 2006, the video game industry generated revenue of close to twelve and a half billion dollars, exceeding the previous record of around two billion dollars. These figures alone might be reason enough to interest someone in learning XNA and becoming a game developer, trying to get a share of a market that’s more profitable than the Hollywood moviemaking one. But let’s be fair and not hide the facts. Unfortunately, there are few openings in this area— about one game programming job per every thousand “real-life” programming jobs. Worse than that, on average, the game industry pays its programmers less than other industries do. After digesting these facts, if you still think that working as a game developer might be cool and rewarding, then this book is for you! We also have some good news: now that Microsoft has opened its LIVE market to XNA games made by the community, there is a potential market of ten million people for your homemade games! This book has the goal of introducing you to XNA, the cross-platform game programming framework from Microsoft, and also presenting you with basic concepts from the game programming industry, showing how these concepts apply to the XNA world. The samples in this book, which include some complete games, will give you the knowledge you need to create your own simple games.